On a Simple Survey Measure of Individual Risk Aversion - Joop Hartog; Ada Ferrer-i-Carbonell; Nicole Jonker (Center for Economic Studies and ifo Institute (CESifo), 2000)
We ask individuals for their reservation price of a specified lottery and deduce their Arrow-Pratt measure of risk aversion. This allows direct testing of common hy-poth-eses on risk atti-tudes in three datasets. We find that risk aversion indeed falls with income and wealth. Entre-preneurs are less risk averse than employees, civil servants are more risk averse than private sector employees, and women are more risk averse than men. We analyze six different specifications of the lottery question in a single data set and find quite consistent results. We conclude that a simple lottery ques-tion is a promising survey in-strument to extract differ-ences in risk attitudes among individuals.
Keywords: 330